2017
DOI: 10.1111/bjd.15000
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic indicators for mycosis fungoides in a Greek population

Abstract: In our study we validated the current prognostic indicators for MF in a Greek population and identified new potential prognostic factors for survival outcome. Our findings contribute to the ongoing investigation of prognostic indicators of MF, further validation of which is highly needed through prospective studies and among different populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
38
4
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(63 citation statements)
references
References 30 publications
9
38
4
11
Order By: Relevance
“…The 5‐year disease‐specific‐survival (DSS) for patients with stage IA and IB MF from this Greek study were 96% and 90%, respectively, and fell to 83% at 10 years for patients at stage IB. This concurs with the indolent course of early‐stage MF but confirms that in around 10% of patients with stage IB, their disease progresses and they may die from the disease within 5 years from diagnosis .…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…The 5‐year disease‐specific‐survival (DSS) for patients with stage IA and IB MF from this Greek study were 96% and 90%, respectively, and fell to 83% at 10 years for patients at stage IB. This concurs with the indolent course of early‐stage MF but confirms that in around 10% of patients with stage IB, their disease progresses and they may die from the disease within 5 years from diagnosis .…”
mentioning
confidence: 74%
“…Nikolaou et al . report on 473 patients with MF including 389 patients (82·2%) with early‐stage (IA–IIA) and 84 (17·8%) with advanced‐stage (IIB–IVB) disease . This is a higher percentage of patients presenting in early‐stage (82·2%) when compared with previous large reports from single centres; 70·7% of 1502 patients and 71·5% of 1263 patients .…”
mentioning
confidence: 85%
“…Given the vast diversity of treatment modalities, ranging from topical corticosteroids to chemotherapies, it is critical to stratify patient to receive treatments most suitable for their circumstances. In recent decade, several studies involving multiple established cutaneous lymphoma groups have investigated clinical factors that have significant prognostic values (Agar et al, 2010;Benton et al, 2013;Nikolaou et al, 2017;Scarisbrick et al, 2015). However, beyond clinical and pathological factors, there are very limited biomarkers available for diagnosis and prognosis of CTCL (Litvinov et al, 2010(Litvinov et al, , 2017Scarisbrick et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several cohort studies that reported on a significant association between old age and OS failed to do so for DSS. 17,19,25 In other studies, older age was correlated with poor DSS in univariate analysis but not in multivariate analysis. 7,22 In our study in elderly patients, advanced age was associated with reduced OS, but not with DSS or PFS in both univariate and multivariate analysis.…”
Section: Discussionmentioning
confidence: 77%
“…The association between advanced age and DSS has been less consistent. Several cohort studies that reported on a significant association between old age and OS failed to do so for DSS . In other studies, older age was correlated with poor DSS in univariate analysis but not in multivariate analysis .…”
Section: Discussionmentioning
confidence: 86%